Depositional Environments and Soft Sediment Deformation in the Early Jurassic Ammonitico Rosso Formation of Western Greece - Vasilis Golfinopoulos; David J. W. Piper; Avraam Zelilidis; Georgia Pe-Piper; Penelope Papadopoulou; Nicolina Bourli; George Iliopoulos (Geosciences)
This study investigates the depositional environments and soft sediment deformation within the Early Jurassic Ammonitico Rosso Formation in the External Ionian Basin (Western Greece), focusing on its biostratigraphy, sedimentology, and tectonic activity. This research provides new insights into the depositional environment of the Ammonitico Rosso Formation and its transitions with the underlying and overlying formations. Syn-rift tectonics at the time of deposition formed half-grabens, which influenced sedimentary processes and created conditions for seabed slumping. Detailed field mapping and microfacies analysis revealed two distinct depositional environments: deep-water to open-shelf settings and platform-margin reefs. The entire Ammonitico Rosso Formation is allochthonous, deposited as repetitive slices of little-disturbed stratified sediments capped by debrites near the toe of a complex submarine landslide. The presence of well-preserved fossils, such as planktonic and benthic foraminifera, Radiolaria (both Spumellaria and Nassellaria), and ammonites, allowed precise age determinations, suggesting that the first appearance of Globuligerina might predate previous records, occurring first in the Pliensbachian rather than the Toarcian. These findings contribute to the ongoing debate on the depth and conditions of Ammonitico Rosso deposition, supporting the hypothesis of a relatively deep, open-shelf environment influenced by slope instability.